2005
DOI: 10.1007/s00198-004-1720-4
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle factors affecting heel ultrasound in Greek females across different life stages

Abstract: The use of quantitative ultrasound (QUS) of the bone is rapidly gaining in popularity, and QUS is widely used worldwide for the assessment of skeletal status. Although much has been learned about the influence of various factors on ultrasonic parameters in various populations, similar information at the local level is not available. This study was carried out to examine the effects of anthropometric, dietary, physical activity, reproductive, and other lifestyle factors on QUS parameters in healthy Greek women,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
55
2
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 50 publications
6
55
2
4
Order By: Relevance
“…In these cases, bone mineral would be directly influenced to a greater extent than would otherwise occur in the normal hormonal environment. In some of the European studies [9], the inverse association with age at menarche was present for all three QUS measures, while other European and Saudi Arabian studies showed associations with BUA but not with SOS and QUI [35, 39]. In Asian Americans [41], no relationship was demonstrated.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In these cases, bone mineral would be directly influenced to a greater extent than would otherwise occur in the normal hormonal environment. In some of the European studies [9], the inverse association with age at menarche was present for all three QUS measures, while other European and Saudi Arabian studies showed associations with BUA but not with SOS and QUI [35, 39]. In Asian Americans [41], no relationship was demonstrated.…”
Section: Discussionmentioning
confidence: 98%
“…BMI has been found to be consistently associated with bone mineral measurements by DXA [5], but QUS associations with BMI have not been as consistent. Positive associations of BUA and SOS with BMI have been demonstrated in different pre-menopausal populations including European women [9, 12], Arabian women [39], and white and African-American women [13, 38]. However, the multicenter European OPUS study [40], the ESOPO study of Italian women [35], and studies of Turkish women [18] did not find a significant association of QUS measures with BMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies show increased bone mass in obese children [54, 55], while others report no difference or decreased bone mass (e.g., decreased total body bone mineral apparent density) after adjusting for body size or weight [44, 56, 57]. Similarly, not all studies have reported beneficial effects of obesity on bone changes measured using QUS [53, 5759]. This may be associated with technical differences among different QUS devices and with whether adjustment for body size or heel width for calcaneal measurement was carried out in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were not significantly changed when we adjusted for heel width or sex-specific stature-forage (i.e., stature z-scores) in our analyses (data not shown). In addition, the effect of body mass appears to be parameter specific [59]. Obese children tend to show advanced growth and maturation possibly resulting in larger bone size and bone mass, compared with normal weight children [54].…”
Section: Discussionmentioning
confidence: 99%